Um objeto de aprendizagem para a óptica no Ensino Médio - Sigwalt, Eduardo Sá Brito (2016)
Technological advances affect many aspects of society. In the educational sphere these innovations have allowed wide access to information from different levels of quality and complexity. Given that the use of technology as a teaching and pedagogical resource can contribute to the construction and socialization of knowledge, allowing greater quality in teaching and learning processes, we sought to, in this research, produce educational materials hosted on the web, based on the theory of David Ausubel through the work of M. A. Moreira. Our goal is to inspire and to facilitate the use of learning objects in the teaching of optics. In fact, there is a large number of websites and free education portals for teaching Physics; however, there is little analysis of how to combine these teaching tools in order to improve Physics teaching. We investigate, with twenty teachers from the city of Curitiba, which features they deem necessary to feature in teaching materials in such content approach. The collected data contributed to the building of a website containing suggestions for didactic sequences, including study guides, educational videos, exercises, recommended websites, and simulators. The developed product constitutes an educational object tailored for both teachers and students. Its main goal is to provide better conditions for the teaching of optics at high school level.